Analysis of serum metabolome of workers occupationally exposed to hexavalent chromium: A preliminary study. (1st October 2021) - Long, Changmao; Hu, Guiping; Zheng, Pai; Chen, Tian; Su, Zekang; Zhang, Yali; Ding, Chunguang; Peng, Fangda; Yu, Shanfa; Wang, Tiancheng; Jia, Guang
Graphical abstract: Highlights: Lipid metabolism and amino acid metabolism were significantly dysregulated in chromate-exposed workers. High resolution mass spectrometry and bioinformatics are conducive to characterize metabolic changes. The decrease of serum l -arginine, PC(18:2/24:4) and PC(14:0/16:0) levels were associated with the WB-Cr in all subjects. The correlations of WB-Cr levels with key differential metabolites were observed in male-only subgroups. Abstract: Hexavalent chromium (Cr(VI)) compound is considered as a common environmental and occupational pollutant due to widespread application in industry and agriculture. Cr(VI) as a carcinogen poses a serious threat to human health and the underlying mechanisms need further investigation. Previous studies had demonstrated the characteristic expression profiling after Cr(VI) treatment in vitro and in vivo at the levels of gene and protein. The comprehensive metabolic signatures were also conducive to discover potential biomarkers for effects assessment of Cr(VI) toxicity. In the current study, Ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS) non-targeted metabolomics was applied to analyze serum metabolic changes in 77 chromate exposure workers and 62 controls. Thirteen metabolites were found significantly decreased and 41 metabolites were increased, which were involved in arginine and proline metabolism, and glycerophospholipid metabolism by bioinformatic analysis. Furthermore, there were significant negative correlations between blood Cr level and Arginine, PC(18:2/24:4) and PC(14:0/16:0), subgroup analyses indicated that these correlations were observed in male-only subgroups, and were not found among chromate workers and controls separately. Diet could be a potential confounder which was not controlled rigorously in this study. These findings provided preliminary clues to investigate the underlying mechanisms of Cr(VI)-induced toxicity and were required to be further verified in future researches.